Flow dependence of wintertime subseasonal prediction skill over Europe - C. Ardilouze (Copernicus Publications, 2021)
Issuing skillful forecasts beyond the typical horizon of weather predictability remains a challenge actively addressed by the scientific community. This study evaluates winter subseasonal reforecasts delivered by the CNRM and ECMWF dynamical systems and identifies that the level of skill for predicting temperature in Europe varies fairly consistently in both systems. In particular, forecasts initialized during positive North Atlantic Oscillation (NAO) phases tend to be more skillful over Europe at week 3 in both systems. Composite analyses performed in an atmospheric reanalysis, a long-term climate simulation and both forecast systems unveil very similar temperature and sea-level pressure patterns 3 weeks after NAO conditions. Furthermore, regressing these fields onto the 3-weeks-prior NAO index in a reanalysis shows consistent patterns over Europe but also other regions of the Northern Hemisphere extratropics, thereby suggesting a lagged teleconnection, related to either the persistence or recurrence of the positive and negative phases of the NAO. This teleconnection, conditioned to the intensity of the initial NAO phase, is well captured by forecast systems. As a result, it is a key mechanism for determining a priori confidence in the skill of wintertime subseasonal forecasts over Europe as well as other parts of the Northern Hemisphere.